PROSEDUR PELAKSANAAN EVENT OLEH BANQUET DI THE ZURI HOTEL PEKANBARU SELAMA MASA PANDEMI COVID-19 - Sara Ashara Rangkuti; Musadad " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research motivated by  carrying out events by banquets, the application of procedures is important as a guide to anticipate various kinds of unexpected situations that will be faced by the hotel as well as a reference for carrying out work. Implementing the right procedures in running an event will greatly facilitate the banquet employees in completing their work.In this study, the authors use descriptive qualitative methods, this method will assist researchers in providing an overview, conditions or phenomena needed by researchers. The technique used by the author in collecting data is observation, interviews, literature study and documentation of the Banquet Manager and Supervisor of The Zuri Hotel Pekanbaru.The results of this study indicate that the implementation of the event by The Zuri Hotel Pekanbaru's banquet runs according to the established procedures although there are still some obstacles such as changes in layout, lack of order, lack of staff and miss communication between banquet employees.   Keywords: Procedure, Event, Banquet